Guiding or Following the Crowd? Strategic Communication as Reputational and Regulatory Strategy. (13th April 2021) - Müller, Moritz; Braun, Caelesta
Abstract: A recently emerging literature demonstrates that reputational concerns explain why regulatory agencies strategically communicate and engage with their manifold audience. We complement this literature by examining the potential of strategic communication as a reputational and regulatory strategy. Based on a reputational approach to public agencies, we assume agencies to strategically diversify between proactively or reactively engaging with public concerns raised by their audiences, depending on whether a core or evolving competency is at stake. We test these assumptions empirically by examining frame alignment between formal communication of the European Central Bank (ECB) and public concerns raised by ECB audiences. Our analysis yields two key findings. First, our findings indicate external frame alignment signaling a strategic reactive strategy by the ECB to diversify its timing in responding to concerns raised by its audiences. Second, we find a pattern of internal frame alignment between the ECB's core competencies and evolving competencies, indicating strategic linkage of attention to various competencies. Our study demonstrates how analyzing an agency's formal communication in tandem with public concerns of its audiences via machine learning techniques can significantly improve our understanding of agency responsiveness and yields significant insights into the democratic legitimacy of regulatory agencies.